2020
DOI: 10.1039/d0qo00658k
|View full text |Cite|
|
Sign up to set email alerts
|

Hydride transfer enabled switchable dearomatization of indoles in the carbocyclic ring and the pyrrole ring

Abstract: The hydride transfer enabled the first success of the regioselective dearomatization of indoles in the carbocyclic ring and the pyrrol ring, which was induced by ortho-quinone methides and vinylogous iminium...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…In 2020, we collaborated with Xiao's group and reported the hydride transfer-enabled, regioselective dearomatization of indoles 68 in the carbocyclic ring and the pyrrole ring (Scheme 14). 19 To dearomatize the carbocyclic ring of indoles, an activating and directing hydroxy group was introduced to the carbocyclic ring of indole. In addition, screening of the reaction conditions showed that the addition of 5 Å molecular sieves and a ligand was essential for reaction efficiency.…”
Section: Quinone Methides As Hydride Acceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, we collaborated with Xiao's group and reported the hydride transfer-enabled, regioselective dearomatization of indoles 68 in the carbocyclic ring and the pyrrole ring (Scheme 14). 19 To dearomatize the carbocyclic ring of indoles, an activating and directing hydroxy group was introduced to the carbocyclic ring of indole. In addition, screening of the reaction conditions showed that the addition of 5 Å molecular sieves and a ligand was essential for reaction efficiency.…”
Section: Quinone Methides As Hydride Acceptorsmentioning
confidence: 99%
“…9 Recently, a conceptually new hydride transfer-involved dearomatization, which combines two hot research fields of dearomatization and direct C(sp 3 )-H functionalization in a single reaction, has drawn much attention from chemists. [10][11][12][13][14][15][16][17][18][19] This "two-birds-with-one-stone" strat- egy opens a powerful avenue to not only streamline the synthesis of previously challenging target molecules but also prepare unreported structurally novel skeletons. In the past few years, with an ever-growing understanding of this rising area, our group have dedicated and made contributions to the hydride transfer-involved dearomatization reactions.…”
Section: Yao-bin Shenmentioning
confidence: 99%
“…Recently, Xiao’s group reported the first regioselective dearomatization between 4-hydroxindoles 43 or 4-hydroxycarbazole 45 and 2-aminobenzaldehydes 42 to construct spiro-tetrahydroquinolines via an aromatization-driven hydride shift strategy ( Scheme 6 ) ( Duan et al, 2020b ). Under the catalysis of scandium complex and HFIP, a variety of spirocyclic molecules incorporating indoles and carbazole moieties were provided with moderate to high yields, respectively.…”
Section: The Construction Of a Spiro-tetrahydroquinoline Skeleton Con...mentioning
confidence: 99%
“…2 Traditionally, there are three general approaches for the assembly of spiroindolenine skeletons, including intramolecular cyclization, 3 in situ [n + 2]-cycloaddition, 4 and direct spiroannulation (DSA). 5 Among these, the DSA strategy has attracted a lot of synthetic interest owing to the advantage of high efficiency and readily available feedstocks. 6 In general, this method usually relies on the sequential double alkylation reactions of indole derivatives with dielectrophiles.…”
mentioning
confidence: 99%